2007
DOI: 10.1002/casp.906
|View full text |Cite
|
Sign up to set email alerts
|

Charitable giving: the effectiveness of a revised theory of planned behaviour model in predicting donating intentions and behaviour

Abstract: A revised theory of planned behaviour (TPB) model was used to determine the influence of attitudes, norms (injunctive, descriptive, and moral norms), perceived behavioural control, and past behaviour on intentions to donate money to charitable organisations.Respondents (N = 227) completed a questionnaire assessing the constructs of the revised TPB model. Four weeks later, a subsample of respondents (N = 67) reported their donating behaviour. Hierarchical multiple regression analyses revealed support for the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
378
10
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(466 citation statements)
references
References 37 publications
35
378
10
15
Order By: Relevance
“…The authors acknowledge that intentions are not the same as actual behaviours. However, research conducted in the context of prosocial interactions has shown how intentions are strongly indicative of actual behaviour (e.g., Smith & McSweeney, 2007). To strengthen the current findings it would be important to replicate the study by employing mixed methodologies, including observational designs (Duffy & Nesdale, 2012) and peer-nomination (Salmivalli, 2010;Monks, Smith & Swettenham, 2003;Obermann, 2011).…”
Section: Limitations and Future Directionsmentioning
confidence: 71%
“…The authors acknowledge that intentions are not the same as actual behaviours. However, research conducted in the context of prosocial interactions has shown how intentions are strongly indicative of actual behaviour (e.g., Smith & McSweeney, 2007). To strengthen the current findings it would be important to replicate the study by employing mixed methodologies, including observational designs (Duffy & Nesdale, 2012) and peer-nomination (Salmivalli, 2010;Monks, Smith & Swettenham, 2003;Obermann, 2011).…”
Section: Limitations and Future Directionsmentioning
confidence: 71%
“…Similar to studies from numerous countries, individuals believe that government should be doing more to help those in need rather than solely depending on the public to do so (Hall et al, 2000). Along a similar vein, donors who have a negative image towards charities also share the perspective that government responsibility towards charities is lacking (Smith and McSweeney, 2007). While the relationship may not be causal, it can be argued that donors hold negative views towards the lack of government support and input into charities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, age has been investigated without conclusive results, some studies found that younger individuals are less likely to donate (Smith and McSweeney, 2007), while others found it be insignificant when considering donor characteristic (Louie and Obermiller, 2000).…”
Section: Donor Characteristicsmentioning
confidence: 99%
“…However, the costs of a donation sometimes involve more than just money. Smith and McSweeney's [59] study shows that physical discomfort deters philanthropy, and that people are more likely to give when they perceive that there are fewer obstacles.…”
Section: Costs and Benefitsmentioning
confidence: 99%